0216 Occupational radiation doses in nuclear medicine: a us multi-centre study. (21st August 2017) - Villoing, Daphnee; Yoder, R Craig; Passmore, Christopher; Bernier, Marie-Odile; Linet, Martha; Kitahara, Cari M
Abstract : Nuclear medicine techniques developed in the second half of the 20th century have become very sophisticated and have been used extensively in the diagnosis and treatment of disease. A surge of new dedicated radiopharmaceuticals and increased demand has led to a growing interest regarding increasing radiation exposure and possible associated health risks to the nuclear medicine technologists who perform these procedures. However, to date, very limited information has been provided on radiation doses received by nuclear medicine technologists. In this study, we collected annual and lifetime badge dose information for United States technologists certified in nuclear medicine between 1979 and 2015. Nine large US medical institutions from several geographical locations contributed information on 208 nuclear medicine technologists, linked to historical badge dose records maintained by a major commercial dosimetry company, yielding 2618 total dose records. The mean and median annual badge doses per technologist were 2.7 and 2.2 mSv, respectively, and more than 3% of the annual doses exceeded 10 mSv. The mean annual doses substantially increased around the year 2000, consistent with the expanded use of Positron Emission Tomography (PET). Mean and median lifetime doses of 51.4 and 32.9 mSv could be established for 45 technologists. Doses in this sample of nuclear medicine technologists were higher than expected, compared with previously published values for nuclear workers or radiologic technologists. These results suggest that nuclear medicine technologists may be one of the most highly-exposed radiation worker populations currently.